Cochlear Implantation in Patients With Intracochlear and Intralabyrinthine Schwannomas. Issue 6 (July 2016) - Carlson, Matthew L.; Neff, Brian A.; Sladen, Douglas P.; Link, Michael J.; Driscoll, Colin L.
Abstract : Objective: Schwannomas may arise primarily within the inner ear, or invade the cochlea or labyrinth from the distal internal auditory canal through transmodiolar or transmacular extension, respectively. To date, very limited data exists regarding cochlear implant (CI) outcomes in this unique population. Study Design: Retrospective case review. Patients: Ten ears (nine patients) with inner ear schwannomas that underwent CI at a single tertiary referral center. Intervention(s): Cochlear implantation. Main Outcome Measure(s): Surgical approach, CI performance. Results: Ten ears (nine patients) were implanted with conventional CI arrays. Three cases had primary inner ear schwannomas, while seven were in patients with neurofibromatosis type 2 (NF2) having transmodiolar invasion of the inner ear from a vestibular schwannoma (VS). In all cases, intracochlear tumor was left in situ to preserve cochlear anatomy and a full electrode insertion was achieved. Use of a styleted electrode with late deployment aided advancement through the intracochlear tumor. In all cases, the ipsilateral internal auditory canal and inner ear could be visualized on postoperative magnetic resonance imaging (MRI) for tumor surveillance. Eight ears achieved good open-set word recognition (median, Consonant-Nucleus-Consonant [CNC] 50% [range, 28–88%], median, AzBio 73% [range, 60–91%]); two patients with NF2 and prolonged deafness (15 and 22 years) received limited benefit. Conclusions: Cochlear implantation in patients with inner ear schwannomas and an intact cochlear nerve is feasible. Leaving intracochlear schwannoma in situ preserves cochlear architecture and use of a styleted electrode may aid in achieving a full insertion when obstructing tumor is present. Postoperative MRI surveillance is still adequate after CI and a high percentage of patients achieve good open-set speech perception performance.